INFILTRATION OF AQUEOUS FLUID AND HIGH FLUID: ROCK RATIOS DURING GREENSCHIST FACIES METAMORPHISM: A REPLY - Ferry J.M. (My University, 1986)
Wood & Graham (1986) suggest that fluid: rock ratios of Ferry (1984) were over-estimated because the temperature of the biotite isograd, inferred from biotite-garnet and calcite-dolomite geothermometry, was underestimated by {small tilde}40°C. Wood & Grahams critique of calcite-dolomite geothermometry is incomplete because it fails to account for the effect of MnCO3 substitutions in calcite on estimated temperatures. New data that consider the effects of both FeCO3 and MnCO3 substitutions suggest that published calcite-dolomite temperatures need no significant correction. Their proposed correction to biotite-garnet temperatures, based on the garnet solid solution model of Ganguly & Saxena (1984), has an uncertainty of at least 100 per cent and is not significantly different from zero. An empirical scheme that corrects for the effects of grossular and spessartine substitution in garnet on estimated temperature, along with the large uncertainty in Wood and Grahams proposed correction, suggest that published biotite-garnet temperatures also need no significant revision. The preferred temperature for the biotite isograd remains {small tilde}400°C. In turn, the preferred estimates of fluid: rock ratios remain unchanged; pelitic phyllites interacted with at least 1-2 rock volumes fluid during the biotite-forming reaction at 400°C. Varied geologic, petrologic, and isotopic data are reviewed that support fluid:rock ratios > 1 during low-grade metamorphism both in south-central Maine and worldwide. Chemical interaction between rocks and fluids that are initially out of equilibrium may be an essential driving force behind many instances of low-grade regional metamorphism. Fluid:rock ratios > 1 and recent stable isotope studies should encourage serious consideration of a multi-pass model for metamorphic fluid flow.